Ocular Hypertension: General Characteristics and Estimated Cerebrospinal Fluid Pressure. The Beijing Eye Study 2011 - Jonas, Jost B.; Wang, Ningli; Wang, Ya Xing; You, Qi Sheng; Yang, Diya; Xu, Liang (PloS one, 2014)
To examine characteristics of ocular hypertensive subjects and potential associations with estimated cerebrospinal fluid pressure (estCSFP). The population-based Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6±9.8 years. Ocular hypertension was defined as intraocular pressure (IOP) >21 mmHg, normal optic nerve head appearance and normal retinal nerve fiber layer thickness. IOP was corrected for its dependence on central corneal thickness (CCT) and corneal curvature radius. Estimated CSFP was calculated as CSFP [mmHg] = 0.44×Body Mass Index [kg/m2]+0.16×Diastolic Blood Pressure [mmHg]-0.18×Age [Years]-1.91. Estimated trans-lamina cribrosa pressure difference (estTLCPD) was IOP-estCSFP. EstCSFP (10.5±3.6 mmHg versus 9.0±3.7 mmHg; P = 0.003) and estTLCPD (12.0±4.4 mmHg versus 5.4±3.8 mmHg; P<0.001) were higher in the ocular hypertensive group than in the normotensive group. In binary regression analysis, ocular hypertension was associated with increased estCSFP (P = 0.03; odds ratio (OR): 1.08; 95% confidence interval (CI): 1.01, 1.17) after adjusting for prevalence of arterial hypertension (P = 0.07; OR: 1.79; 95%CI: 0.96, 3.34), retinal nerve fiber layer thickness (P = 0.03; OR: 0.97; 95%CI: 0.95, 0.997) and blood glucose concentration (P = 0.006; OR: 1.17; 95%CI: 1.04, 1.30). Ocular hypertensive subjects (with IOP correction for CCT and corneal curvature) as compared to ocular normotensive subjects had a significantly higher estCSFP in univariate analysis and in multivariate analysis. Despite of a higher estCSFP, estTLCPD was still markedly higher in ocular hypertensive eyes than in ocular normotensive eyes.